2021
DOI: 10.3390/proteomes9010008
|View full text |Cite
|
Sign up to set email alerts
|

Exosome-Derived Mediators as Potential Biomarkers for Cardiovascular Diseases: A Network Approach

Abstract: Cardiovascular diseases (CVDs) are widely recognized as the leading cause of mortality worldwide. Despite the advances in clinical management over the past decades, the underlying pathological mechanisms remain largely unknown. Exosomes have drawn the attention of researchers for their relevance in intercellular communication under both physiological and pathological conditions. These vesicles are suggested as complementary prospective biomarkers of CVDs; however, the role of exosomes in CVDs is still not full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 119 publications
0
21
0
Order By: Relevance
“…Notably, Moreira-Costa et al performed a literature search and network analysis to evaluate the interaction between exosomes and cardiovascular diseases [ 21 ]. For CAD patients, up-regulated exosomal proteins, including fibrinogen beta/gamma chain, inter-alpha-trypsin inhibitor heavy chain, and alpha-1 antichymotrypsin, were assessed as putative protein biomarkers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, Moreira-Costa et al performed a literature search and network analysis to evaluate the interaction between exosomes and cardiovascular diseases [ 21 ]. For CAD patients, up-regulated exosomal proteins, including fibrinogen beta/gamma chain, inter-alpha-trypsin inhibitor heavy chain, and alpha-1 antichymotrypsin, were assessed as putative protein biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…For CAD patients, up-regulated exosomal proteins, including fibrinogen beta/gamma chain, inter-alpha-trypsin inhibitor heavy chain, and alpha-1 antichymotrypsin, were assessed as putative protein biomarkers. Several down-regulated proteins were also considered relevant to CAD, such as albumin, clusterin, and vitamin-D-binding protein [ 21 ]. While our findings provide essential information for the involvement of exosomal miRNAs in stable three-vessel CAD, their results shed light on the possible validation of miRNAs and exosome-originated protein in combination with the novel biomarkers of CAD [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, even though its role in HF is still unknown and it is upregulated in patients with HF, exo-miRNA-92a has been proposed as a clinical biomarker because of its upregulation in patients with HF, high sensitivity/sensibility, and correlation with echocardiographic indices for LV dilation and dysfunction [ 82 ]. It is noteworthy that a recent study calls into question the exosomal origin of miRNA-92a, warranting further investigations [ 83 ]. Overall, the confirmation of miRNAs presence in exosomes together with the knowledge of their function in HF pathogenesis are emerging as important starting points for the clinical translation of exo-miRNAs.…”
Section: Exosomesmentioning
confidence: 99%
“…Another study found that pharmacological inhibition of miR-146a via antagomir injection attenuated cardiac dysfunction and inhibited cardiac remodeling in rats with MI-induced HF [ 87 ]. Previous studies have shown that miR-146a can be used as a potential biomarker to evaluate the efficacy of anti-HF agents [ 88 ].…”
Section: 4 Micrornas As a New Modulator Of Calcium Signaling Pathwaymentioning
confidence: 99%